H2O & the Waters of Forgetfulness - Illich, Ivan (London Marion Boyars, 1986)
Philosopher and social analyst Ivan Illich, one of the most influential thinkers of second half of this century, directs his attention to water, the 'stuff' of purity and the creative force of the imagination without which life in unthinkable. He deals with the dual nature of water, as life-giving material substance and as the wellspring of form, on which are founded the most basic myths and cultural manifestations: water as cleanser, water as domestic necessity and water as a religious and spiritual force.